Cost-utility analysis of Palbociclib + letrozole and ribociclib + letrozole versus Letrozole monotherapy in the first-line treatment of metastatic breast cancer in Iran using partitioned survival model - Ali Darvishi; Rajabali Daroudi; Ali Akbar Fazaeli (Health Economics Review, 2023)
Abstract Background Palbociclib and Ribociclib are cyclin-dependent kinase 4/6 oral molecular inhibitors that have the potential to improve overall survival (OS), progression-free survival (PFS), and quality of life in patients with metastatic breast cancer (MBC). The objective of this study was to analyze the cost-utility of Palbociclib and Ribociclib in comparison with Letrozole monotherapy as the first-line treatment for hormone receptor-positive (HR+)/human epidermal growth factor receptor 2-negative (HER2–) MBC patients in Iran. Methods A Cost-Utility Analysis (CUA) was conducted using a partitioned survival model (PSM) from the perspective of the Iranian healthcare system. The comparative strategies considered were Palbociclib + Letrozole, Ribociclib + Letrozole, and Letrozole monotherapy. The model was structured with a 1-month cycle length and a 15-year time horizon. Clinical safety, efficacy, and survival data in terms of PFS and OS for Palbociclib + Letrozole and Ribociclib + Letrozole were obtained from the latest updates of the PALOMA-1, 2, and MONALEESA-2 studies, respectively. Direct medical costs, including drug costs, visits, hospitalization, CT scans, bone x-rays, monitoring and laboratory testing, as well as medication side effects, were considered. Uncertainty evaluations were performed through deterministic sensitivity analysis and probabilistic sensitivity analysis. Excel 2016 and TreeAge 2020 were used for all stages of the evaluation. Results The base case results indicated that, despite its lower effectiveness, Letrozole monotherapy was the most cost-effective strategy, while Palbociclib + Letrozole and Ribociclib + Letrozole were not cost-effective. The incremental cost-effectiveness ratios (ICERs) for Palbociclib + Letrozole and Ribociclib + Letrozole compared to Letrozole monotherapy were estimated at $137,302 and $120,478 per quality-adjusted life-year (QALY), respectively, which exceeded the target threshold of $4565. Deterministic sensitivity analysis demonstrated that the CUA results were not sensitive to changes in the values of uncertain variables. Probabilistic sensitivity analysis also indicated that Palbociclib + Letrozole and Ribociclib + Letrozole had no chance of being cost-effective based on changes in various parameters and simulations. Conclusions Palbociclib and Ribociclib showed significant efficacy in combination with Letrozole, as evidenced by improvements in PFS. However, in the first-line treatment of MBC in Iran, these strategies were not cost-effective compared to Letrozole monotherapy.